Numerical Characterisation of Jet-Vane based Thrust Vector Control Systems - Chandra Murthy, M.S.R.; Chakraborty, Debasis (Defence Science Journal, 2015)
Computational fluid dynamics methodology was used in characterising jet vane based thrust vector control systems of tactical missiles. Three-dimensional Reynolds Averaged Navier-Stokes equations were solved along with two-equation turbulence model for different operating conditions. Nonlinear regression analysis was applied to the detailed CFD database to evolve a mathematical model for the thrust vector control system. The developed model was validated with series of ground based 6-Component static tests. The proven methodology is applied toa new configuration. Defence Science Journal, Vol. 65, No. 4, July 2015, pp. 261-264, DOI: http://dx.doi.org/10.14429/dsj.65.7960